Eco-efficiency analysis of non-potable water systems in domestic buildings. (15th September 2017) - Lam, Chor-Man; Leng, Ling; Chen, Pi-Cheng; Lee, Po-Heng; Hsu, Shu-Chien
Highlights: This study developed an eco-efficiency analysis (EEA) framework for evaluating water reuse systems. Four water management scenarios were analyzed in a case study in Hong Kong. Decentralized anaerobic fluidized be membrane bioreactor (AFMBR) system is the most eco-efficient scenario. The EEA framework can be a basis for further application of greywater recycling systems. Abstract: Energy efficiency in water systems contributes significantly towards achieving sustainable water management. Decentralized anaerobic fluidized bed membrane bioreactor (AFMBR) systems with energy recovery have been proposed for greywater recycling in domestic buildings for non-potable uses, such as toilet flushing. This study developed an eco-efficiency analysis (EEA) framework with the integration of life-cycle assessment (LCA) and economic analysis for the evaluation of different water systems. Four water management scenarios including (1) freshwater flushing system, (2) seawater flushing system, (3) greywater flushing system adopting aerobic membrane bioreactor (MBR), and (4) greywater flushing system adopting AFMBR, were analyzed in a case study in Hong Kong. The EEA results reveal the AFMBR greywater reuse scenario to be the most eco-efficient option as the system is capable of energy recovery, recycling of water resource and reduction of sewage treatment loadings. This study has demonstrated that the EEA framework is an effective tool to guide water management towards sustainability and provides a basis for further research on the application of greywater recycling systems on a larger scale.